Thermal niche for seed germination of Xyris species from Brazilian montane vegetation: Implications for climate change. Issue 2 (26th January 2021) - Oliveira, Túlio G. S.; Duarte, Alexandre A.; Diamantino, Isabela P.; Garcia, Queila S.
Abstract: Understanding how climate change will affect regeneration from seeds is important for developing conservation strategies. We evaluated seed germination requirements for sympatric species of Xyris from montane rupestrian grasslands ( campo rupestre ) in Brazil to determine their thermal niche and thermal requirements for seed germination. We also assessed whether projected temperature increases would affect seed germination of the species. Seed germination was evaluated at a wide range of constant temperatures (10–40°C) under light (12‐hr photoperiod) and dark conditions. Base temperatures ( Tb ) and thermal times for 50% germination ( θ 50 ) were calculated for three species. The effects of projected mean temperature increase on seed germination percentage and timing were evaluated. All species revealed an absolute light requirement for germination. Thermal germination niche breadth was greatest for X. asperula (15 to 35°C) and narrowest for X. seubertii (20 and 25°C). Base temperatures for X. asperula, X. pilosa and X. trachyphylla were 9.0, 12.8 and 11.1°C, respectively. In the scenario with the highest temperature increase (A2), the greatest reductions in seed germination are observed for X. pilosa and X. seubertii . The lowest projected temperature increase (2°C) was sufficient to decrease by 1 day the germination time of X. asperula and X. pilosa . Species of Xyris do not present a pattern for thermal germination niche and thermal requirements values, indicating that the effects of climate warming on the regeneration of these seeds will probably vary among species. Abstract : Neotropical species of Xyris have different thermal requirements for seed germination. Sensitivity to climate change during germination varies among species.